La charge mentale. Histoire d'une notion charnière (1976-2020) - Haicault, Monique (2020)
La notion est née au milieu des années 1970 dans le cadre d’un enseignement universitaire de sociologie et de recherches sur le travail des femmes et la division sexuée des activités identifiées dans toutes les sphères sociales, celle de la production des biens et celle de la production/reproduction des personnes.
Keywords: approches et analyses; capitalisme; charge mentale; discipline; histoire et politique; inégalités; projet charge mentale; rapports sociaux de sexe; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis